BPR Siwi Sedana Marketing Communication Strategy in Attracting Customers in the Era of the Covid-19 Pandemic - Dewa Ayu Trisna Adhiswari Wedagama; Komang Ayu Eunike Sukaning Dewi; Kadek Yuni Pratiwi (Universitas Pendidikan Nasional, 2022)
This study discusses the marketing communication strategy at BPR Siwi Sedana during the covid-19 pandemic. As a BPR that has worked for 30 (thirty) years, BPR Siwi Sedana can attract customers and continue to exist in the current pandemic era. This study aims to determine the marketing communication strategy of BPR Siwi Sedana during the pandemic by using the IMC (Integrated Marketing Communication) communication strategy. With this, the researchers used qualitative research methods, and the data collection techniques used in this study were interviews, observation, and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. From the results of the study, it can be concluded that during the COVID-19 pandemic, BPR Siwi Sedana used four marketing mix strategies from the IMC (Integrated Marketing Communication) strategy, namely advertising, sales promotion, personal selling, and interactive marketing in attracting customers.